Crimean Congo Haemorrhagic fever virus in humans, animals and ticks in Kenya - Agwanda, B.; Obanda, V.; Blanco, I.; Lwande, Olivia Wesula (International Livestock Research Institute, 2021)
Kenya One Health Conference, 6-8 December 2021